Billing and online payment portal with multi-factor authentication using one-time password - Mae Reyes Aribon-Libag , Christle (Journal of Advanced Computer Science & Technology, 2024)
NCTVN Cable Network Corporation is a cable/internet distributor in Kidapawan City. Its area of operation covers Makilala, Arakan, Antipas,Matalam, Midsayap,Magpet President Roxas, Kabacan and Kidapawan City. The users of cable and internet rely to them in which they have to extend their services to the Province. By this venture, the number of subscribers of their services has grown and the area covered are widen. Given the number of subscribers there is a need to create a consistent and quick support to their customers in terms of billing presentment and payment. In the current process, Billing and delivery of the statement is one of the challenges they are facing where they usually cover cost for their workforce, paying onsite over the counter of the subscribers takes a lot of time and payment is unsafe if the collector will intend to run the money. NCTVN manual process cannot take it enough to manage their business. The aim of this project is to help the NCTVN Cable Network Corporation by developing billing and online payment portal integrated with multi-factor authentication. There are two way to access the site. First, Web Portal and Second, Mobile Application named NPAy Application (app). The system enables the customer to pay their monthly bill through the use of online payment portal using available merchants like Gcash, Maya, coin.ph and many other as payment gateway with added security features to secure the customer’s information and payment online. The best part of this app is the easiness of the users (referring to admin and customer) to access their NPay app anytime and anywhere as long as the customer is connected with internet, see their monthly bills, pay online and secure the system process and transaction from registration of customer’s account down to the payment process where system will validate or authenticate using One-Time Password (OTP). The App is design to serve one user’s roles: The Subscribers of NCTVN Cable Network Corporation. For the designing and development of the project, PHP has been used for the programming language and MySQL for the integration of database, and this system was hosted in exonhost.com with the live domain name of www.nctvn2022.site as official address. Varieties of methods of testing were applied to test if the anticipated output was effectively delivered. Test results and cases were created and distributed. The outcomes show that the system satisfied the user's expectations and successfully completed the testing phase. Furthermore, this system is optional for the users due to the following factors: First, Subscribers are from far flung barangay with no internet or cellular connection, and no mobile phones or Personal Computer. But for the customers who intend to use it. This system is beneficial to them because the process and customer will experience direct support from the company with the contact less setup, fast, easy-to-used and effective billing and payment portal with security features.